2011
DOI: 10.4103/0019-5413.77134
|View full text |Cite
|
Sign up to set email alerts
|

Bladder management methods and urological complications in spinal cord injury patients

Abstract: Background:The optimal bladder management method should preserve renal function and minimize the risk of urinary tract complications. The present study is conducted to assess the overall incidence of urinary tract infections (UTI) and other urological complications in spinal cord injury patients (SCI), and to compare the incidence of these complications with different bladder management subgroups.Materials and Methods:545 patients (386 males and 159 females) of traumatic spinal cord injury with the mean age of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 24 publications
9
48
0
Order By: Relevance
“…Mainly, moderate rates (4-9%) have been observed in European studies, 2,19,20 whereas in other parts of the world reported TUC rates range from 17 to 41%. 14,15,18 The use of SPC seems to be similar (11-14%) 14,18 or less common (4-9%) 15,19 compared with present data (13%).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Mainly, moderate rates (4-9%) have been observed in European studies, 2,19,20 whereas in other parts of the world reported TUC rates range from 17 to 41%. 14,15,18 The use of SPC seems to be similar (11-14%) 14,18 or less common (4-9%) 15,19 compared with present data (13%).…”
Section: Discussionsupporting
confidence: 53%
“…6,7 The majority of individuals with NLUTD who abandon IC seem to change to indwelling catheterization. 6,7 However, bladder evacuation by indwelling catheterization is associated with an increased risk of serious complications, [8][9][10][12][13][14][15] and thus individuals at risk of changing to indwelling catheterization should be identified and alternative solutions should be offered. In the present study, gender, age, injury severity and injury duration were significant predictors of bladder evacuation by SPC or TUC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guenther et al 10 observed no significant difference in the stricture rates between men using IC (that is, 22%) and men using spontaneous or triggered reflex voiding (that is, 24%). Singh et al 11 reported higher stricture rates with IC (that is, 18%) compared with other evacuation methods, such as normal, spontaneous or reflex voiding and suprapubic catheterization (that is, 2%). However, no statistical comparison was performed between these groups.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 The main body of literature has been published more than a decade ago, and the reported stricture occurrence rate is generally lower (o10%) in earlier investigations [7][8][9] compared with more recent ones (~20%). 10,11 Over the years, different catheter materials and methods have been introduced. The catheter surface has been claimed to be an important factor in the development of urethral strictures.…”
Section: Introductionmentioning
confidence: 99%